Control of Typha by Competitive Plant - Mehta, Indu; Shara, Ram Krishan (Annals of Arid Zone, 2016)
Some experiments have been initiated to control Typha in ,the drainage ditches by planting parallrass (Brachiariamutica Forsk Stapf.), in Chambal Command Area, Kota, Rajasthan. The planting was done at Typha free (after desilting) and Typha infested areas (after cutting leaves), It was observed that in the desilted area, a few Typha plants could grow but their population never increased more than 1.6/m2, In Typha infested area the population of Typha was increasing till 5 months period because upto this period paragrass took time for its establishment. Later on both the horizontal and erect growth of this grass started covering. Typha plants started decreasing and ultimately became almost nil after 10-12 months of planting, In the area where cutting’ of Typha plants was done every month of planting to create worst conditions fort Typha and good conditions for paragrass it took only six months to replace the Typha completely. In addition to control of Typha with this method more than 800 qtl/ha/year green fodder may be obtained, which can give a net profit of Rs. 3000-4000/year from the waste lands.